Pengaruh Strategi Komunikasi Terhadap Kinerja Organisasi Publik - Avent Christy Patiro (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the influence of communication strategies on the performance of public organizations. Communication strategies are an essential element in building coordination, aligning goals, and improving the quality of public services. However, various studies show that public organizations still face serious challenges in the form of miscommunication, ineffective information flow, and low utilization of internal communication media. These conditions impact performance achievement, both in terms of efficiency, program effectiveness, and public satisfaction as service users. This study uses a quantitative approach with a survey method targeting employees of public organizations in a specific area. Data collection was conducted through questionnaires adapted from Cutlip & Center's communication strategy model and Robbins' organizational performance indicators. The data were analyzed using linear regression to examine the influence of communication strategies, including message clarity, communication channels, information transparency, and feedback, on organizational performance. The results of the study indicate that communication strategies have a positive and significant impact on public organizational performance. Message clarity and information transparency are the aspects that contribute the most to performance improvement. These findings affirm that the quality of internal communication is a key factor in creating responsive and effective public organizations. This study provides important implications for public organization management to optimize communication strategies through enhancing human resource capacity, utilizing information technology, and developing more structured communication SOPs